Coping Strategies for Work-Family Conflict among Working Housewives in Cipatujah Village, Tasikmalaya Regency, Indonesia - Kalfin; andrian, riza; Hadiaty, siti (Communication in Research and Publications (CRP), 2023)
This research addresses the escalating phenomenon of working mothers in Indonesia, particularly in Cipatujah Village, Tasikmalaya Regency. With nearly 30 percent of married women engaged in employment, the study focuses on the work-family conflict experienced by these working housewives and aims to uncover their coping strategies. The literature review emphasizes the scarcity of research on coping efforts from the perspective of working women, particularly in developing country contexts like Indonesia. Using a qualitative approach, the study explores the experiences of six working homemakers managing dual roles through observation, interviews, and document analysis. The findings reveal diverse types of work-family conflict, including time-based, strain-based, and behavior-based conflicts. The coping strategies employed by these housewives vary, encompassing problem-focused coping, emotion-focused coping, and a combination of both. This research contributes to the existing literature by providing nuanced insights into the challenges faced by working housewives in a specific rural context. The variations in coping strategies underscore the importance of recognizing individual differences and the complexity of work and family contexts. The study advocates for tailored support systems and policies, considering cultural values and grassroots-level experiences. In conclusion, this research contributes to a comprehensive understanding of coping mechanisms for work-family conflict among working mothers in Indonesia, offering valuable implications for policymakers and future research endeavors.